Islamic Muhtasib and American CPAs: A Comparative Study of Institutions Meant to Protect Public - Athar Murtuza; Wagdy Abdallah (Journal of Accounting, Business and Management (JABM), 2007)
From the 7th to the 17th centuries, various Muslim governments sought to regulate behavior in the marketplace to prevent the exploitation of consumers from fraudulent activities of dishonest merchants and businesses. In Islamic history, marketplace inspection and control to prevent fraudulent exploitation of consumers goes back to the time of Prophet Muhammad [pbuh] and the first four Caliphs. The official in-charge of this function was called Muhtasib. Since Muhtasibs role was to protect public interest, we compare him with contemporary public auditorCPAs. The paper recommends that with adaptation of his role to contemporary environment, Muhtasib could serve as a useful antecedent for more credible accounting and auditing standards in Islamic countries.